Impact of mitochondrial metabolism on T-cell dysfunction in chronic lymphocytic leukemia - Gamal, Wael; Mediavilla-Varela, Melanie; Kunta, Vishaal; Sahakian, Eva; Pinilla-Ibarz, Javier (Frontiers in Cell and Developmental Biology, 2025)
T cells play a central role in anti-tumor immunity, yet their function is often compromised within the immunosuppressive tumor microenvironment, leading to cancer progression and resistance to immunotherapies. T-cell activation and differentiation require dynamic metabolic shifts, with mitochondrial metabolism playing a crucial role in sustaining their function. Research in cancer immunometabolism has revealed key mitochondrial abnormalities in tumor-infiltrating lymphocytes, including reduced mitochondrial capacity, depolarization, structural defects, and elevated reactive oxygen species. While these mitochondrial disruptions are well-characterized in solid tumors and linked to T-cell exhaustion, their impact on T-cell immunity in lymphoproliferative disorders remains underexplored. Chronic lymphocytic leukemia (CLL), the most prevalent chronic adult leukemia, is marked by profound T-cell dysfunction that limits the success of adoptive cell therapies. Emerging studies are shedding light on the role of mitochondrial disturbances in CLL-related T-cell dysfunction, but significant knowledge gaps remain. This review explores mitochondrial metabolism in T-cell exhaustion, emphasizing recent findings in CLL. We also discuss therapeutic strategies to restore T-cell mitochondrial function and identify key research gaps.